Pendidikan Kepemimpinan Dalam Islam (Studi Terhadap Biografi Khalifah Umar bin Khattab) (Indo-MathEdu Intellectuals Journal, 2024)
Umar bin Khattab r.a., is one of the Prophet's companions who is different from everything that was bestowed upon him. This figure seems to never dry up as a source of inspiration and knowledge for many people, always being an object of study and research that attracts the interest of scholars, intellectuals, and scientists. The second caliph after Caliph Abu Bakar r.a., has an extraordinary exemplary portrait in terms of leadership and personality. Umar bin Khattab r.a. as one of the Prophet's companions is known to have extraordinary privileges in all dimensions of his life. While the method used in this study uses a qualitative method. The purpose of this study is to find out during the struggles of Umar bin Khattab during his tenure as Caliph Rasyidin. The results of this study indicate that Caliph Umar was the first person to create an Islamic state document and to manage the Baitul Maal significantly